2019
DOI: 10.3390/cancers11070953
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Development Is Not Affected by Statin Use in Patients with Elevated PSA Levels

Abstract: Background: The role of statins in prostate cancer (PCa) remains unclear. Conflicting evidence has been found concerning risk reduction with the use of statins on biochemical recurrence (BCR). In this study, we evaluated whether statin use decreases the incidence of advanced PCa in males with elevated prostate-specific antigen (PSA; ≥4.0 ng/mL) levels and determined whether statin use reduces the risk of BCR after radical prostatectomy (RP). Methods: Patients visiting the outpatient urology clinic of the VU Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In general, treatment with statins that preceded cancer diagnosis lowers the risk of cancer development and prolongs the overall survival in comparison with statin non-users or patients who started taking statins after a cancer diagnosis. For instance, studies have shown that the use of statins before a diagnosis is associated with a lower risk of pancreatic cancer, 2 non-Hodgkin lymphoma, 3 oesophageal adenocarcinoma 4 and brain cancer 5 but not breast cancer, 12 prostate cancer 6,7 or endometrial cancer. 8 Also, regular statin use before diagnosis modestly prolonged the survival of patients in comparison with non-users or non-regular users in pancreatic cancer, 9 gastric cancer, 10 head and neck squamous cell carcinoma, 11 breast cancers, 12 lung cancer, 13 uterine cervical cancer, 14 prostate cancer, 15 kidney cancer, 16 endometrial cancer 17 and multiple myeloma, 18 but not in colorectal cancer 19 or glioblastoma 20 (see Table 1).…”
Section: Statins In Meta-analyses and Cohort Studiesmentioning
confidence: 99%
“…In general, treatment with statins that preceded cancer diagnosis lowers the risk of cancer development and prolongs the overall survival in comparison with statin non-users or patients who started taking statins after a cancer diagnosis. For instance, studies have shown that the use of statins before a diagnosis is associated with a lower risk of pancreatic cancer, 2 non-Hodgkin lymphoma, 3 oesophageal adenocarcinoma 4 and brain cancer 5 but not breast cancer, 12 prostate cancer 6,7 or endometrial cancer. 8 Also, regular statin use before diagnosis modestly prolonged the survival of patients in comparison with non-users or non-regular users in pancreatic cancer, 9 gastric cancer, 10 head and neck squamous cell carcinoma, 11 breast cancers, 12 lung cancer, 13 uterine cervical cancer, 14 prostate cancer, 15 kidney cancer, 16 endometrial cancer 17 and multiple myeloma, 18 but not in colorectal cancer 19 or glioblastoma 20 (see Table 1).…”
Section: Statins In Meta-analyses and Cohort Studiesmentioning
confidence: 99%
“…A total of 650 records were excluded after reading the title and abstract, and 50 records were excluded for not having full-text or original data. After reading the full text, 31 records were excluded due to lack of data about BCR and two records were excluded because they did not belong to cohort studies (one RCT ( 73 ) and one case–control ( 74 ) study). Finally, 33 studies met the inclusion criteria for the current review.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 27 studies for this meta-analysis, and the flow chart of the search and selection is shown in Figure 1 [10–36] . Specifically, 11484 patients with statin use and 25937 patients without such medication were included; 18 studies evaluated the impact of statin use in patients undergoing RP and 9 studies evaluated the impact of statin use in patients undergoing RT.…”
Section: Resultsmentioning
confidence: 99%